2017
DOI: 10.1111/bjdp.12219
|View full text |Cite
|
Sign up to set email alerts
|

The I in autism: Severity and social functioning in autism are related to self‐processing

Abstract: It is well established that children with autism spectrum disorder (ASD) show impaired understanding of others and deficits within social functioning. However, it is still unknown whether self-processing is related to these impairments and to what extent self impacts social functioning and communication. Using an ownership paradigm, we show that children with ASD and chronological-and verbal-age-matched typically developing (TD) children do show the self-referential effect in memory. In addition, the self-bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
0
29
0
1
Order By: Relevance
“…Of particular relevance to early development, self‐processing issues may be an important element of autism. Studies of children (Gillespie‐Smith, Ballantyne, Branigan, Turk, & Cunningham, ; Henderson et al., ) and adults (Grisdale, Lind, Eacott, & Williams, ; Lombardo, Barnes, Wheelwright, & Baron‐Cohen, ; Toichi et al., ) with autism suggest there may be unusual SRE patterns, which may be symptomatic of disruptions in the SMS (see Lind & Bowler, ). Interestingly, brain imaging studies suggest that adolescents with and without autism show divergent patterns of neural activation when engaged in self‐processing (Pfeifer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to early development, self‐processing issues may be an important element of autism. Studies of children (Gillespie‐Smith, Ballantyne, Branigan, Turk, & Cunningham, ; Henderson et al., ) and adults (Grisdale, Lind, Eacott, & Williams, ; Lombardo, Barnes, Wheelwright, & Baron‐Cohen, ; Toichi et al., ) with autism suggest there may be unusual SRE patterns, which may be symptomatic of disruptions in the SMS (see Lind & Bowler, ). Interestingly, brain imaging studies suggest that adolescents with and without autism show divergent patterns of neural activation when engaged in self‐processing (Pfeifer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Partial correlations, controlling for the influence of all remaining individual differences variables, showed that the magnitude of the SRE increased with better verbal ability and memory span but decreased with better theory of mind, empathy, and recollection. These findings are consistent with the suggestion that the SRE is a complex phenomenon reflecting a competition between factors favouring memory for one's own experiences and those favouring memory for others’ experiences (Cunningham et al ., ; Gillespie‐Smith, Ballantyne, Branigan, Turk, & Cunningham, ). Indeed, the activity used to elicit the SRE in our study might have been especially suited to demonstrating these opponent processes.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the recent findings of Gillespie‐Smith et al . (), for example, while ASD children could lack a well‐developed self‐concept that curbs their elaboration of self‐referential information, this might not manifest as a diminished SRE if, compared to typically developing children, they show less interest in other people.…”
Section: Discussionmentioning
confidence: 99%
“…Such observations are globally also referred to as an impairment in ‘Theory of Mind’ (Baron-Cohen 1997). For the ‘weak self’ part of the paradox, sometimes also called ‘absent self’ (Frith 2003), the key observations concern difficulties with the 1st person pronoun ‘I’, infrequent mention of emotional or cognitive internal states; low introspection, (Gillespie-Smith et al 2018) and limited episodic autobiographical memory (Brown et al 2012). Evidence for both ego-centredness and weak self-referentiality often comes from narrative tasks, in which people with autism, compared to control groups, are found on the one hand less likely to include information that would help listeners, such as temporal references, thus indicating less perspective-taking work, and, on the other, to associate less complex and varied mental and emotional states to both their own or other characters’ actions (see Stirling et al 2014 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from criticism about the adequacy of an all-explanatory, single core deficit in autism (Roth and Rezaie 2011, cit. in Scholiers 2019), experimental findings are contradictory when looking at either narrative abilities (Colle et al 2008) or other types of self-processing tasks (Gillespie-Smith et al 2018), with definitive results about systematic poorer performances in any of those areas not having been ascertained. Secondly, some of the difficulties in communication and social relations reported in children and youth have been often observed to fade or disappear with age or intervention (Vivanti et al 2018), which is at odds with theories of a neurologically-based impairment in those areas.…”
Section: Introductionmentioning
confidence: 99%